Anxiolytic-like effect of Lippia alba essential oil: A randomized, placebo-controlled trial - Soto Vásquez, Marilú Roxana (2018)
Aim: This study was conducted to examine whether aromatherapy with essential oil of Lippia alba can reduce anxiety levels in a normal population. Methods: The oil was extracted by hycirodistillation for 3 hours using a modified Clevenger-type apparatus and then chemical composition was investigated by a corn. bination of gas chromatography analysis and gas chromatography-mass spectrometry. Moreover, a randomized, double blind, placebo-controlled trial was conducted, where 62 participants were divided into two groups, comprising a control group treated with placebo, and an experimental group (EG) treated with aromatherapy based on Lippia alba essential oil. The anxiety index was evaluated pretest by State-Trait Anxiety Inventory. Measures were taken twice: during pretest and posttest. Results: The chemical analysis showed that carvone was the main component (62,8%), State and trait anxiety scores showed a decrease in the posttest study phase in corn. parison with pretest in the EG (p < 0.005 for state anxiety and p < 0.05 for trait anxiety). Cohen's d score was 1.06 in state anxiety, while it was 0,72 for trait anxiety. The percentages of change showed reductions of anxiety variable ranging between 15.50% for state anxiety and 12.25% for trait anxiety. Conclusion: These results suggest that aromatherapy based on essential oil of Lippia alba may be useful as a means to counteract anxiety.